STRATEGI PROMOSI DALAM MENINGKATKAN JUMLAH PENGGUNA LAYANAN AUTO2000 HOME SERVICE (THS) PADA PT ASTRA INTERNATIONAL AUTO2000 SANUR - DEWI, ADE AYU CITRA; WIJAYATI, NI LUH MADE; NARTI, NI KETUT (GANEC SWARA, 2024)
This research was conducted at PT Astra International Auto2000 Sanur which aims to determine the promotion strategy in increasing the number of users of Auto2000 Home Service (THS). Data collection methods used are observation, interviews, documentation, and questionnaires. The analytical techniques used are qualitative descriptive analysis, Internal Factors Analysis Summary (IFAS) Matrix, External Factors Analysis Summary (EFAS) Matrix, Internal-External (IE) Matrix, SWOT Matrix, Quantitative Strategic Planning Matrix (QSPM) analysis. Based on the results of the IFAS matrix analysis, the main strength is that the Auto2000 Home Service (THS) makes it easy for customers to do service anywhere and helps streamline customer time. Meanwhile, the weaknesses are the use of digital marketing which is still lacking and the few promos given. Based on the EFAS matrix analysis, it is known that the main opportunities are the popularity of the Toyota brand and technological developments, while the main threat is the limited coverage area. The results of the IE matrix are in cell I growth. The SWOT analysis resulted in eight alternative strategies and from the eight strategies, two priority strategies were obtained which were calculated through the QSPM matrix with a total TAS value of 6.42 and 6.05, namely increasing promotions on social media (Instagram and Tiktok) to introduce Auto2000 Home Service (THS) services to the target audience.